HUBUNGAN KEKUATAN OTOT LENGAN DAN KOORDINASI MATA TANGAN TERHADAP KETEPATAN SERVIS BOLA VOLI - Rambu Rambu; Abdurrauf Abdul Karim (Journal of Physical Education and Sport Science, 2020)
Eye-hand coordination is a person's accuracy in estimating between eye movements (gaze) and hand movements effectively. The perfection of the lower serve movement is influenced by the level of eye-hand coordination accuracy of the volleyball player. The objectives of this study were: 1) to determine the relationship between arm muscle strength and the ability to serve under the volleyball game for students of SMP Negeri 5 Mimika, Mimika Regency. 2) to know the relationship between hand eye coordination and underservice ability in the volleyball game of SMP Negeri 5 Mimika students. 3) To know the relationship between arm muscle strength and hand eye coordination on lower service ability in volleyball games for students of SMPN 5 Mimika, Mimika Regency This research is a correlational research. The results showed that there was a relationship between arm muscle strength and the accuracy of the lower serve in the volleyball game of SMP Negeri 5 Mimika students, with a value of rx2.y = 0.818> r (0.05) (30) = 0.349, there was a significant relationship between hand eye coordination. with lower service accuracy in the volleyball game of SMP Negeri 5 Mimika students, with a value of rx3.y = 0.515> r (0.05) (30) = 0.349. Oriented to the results of the study, it was found that there was a significant relationship between arm muscle strength and hand eye coordination with the results of lower serve in volleyball games for students at SMP Negeri 5 Mimika, namely the value of Ry (x1.x2.x3) = 0.829> R (0.05) (30 ) = 0.349.